Gender Dynamics in ASEAN Economic Liberalization: The Implications of AFTA on Equality and Women’s Empowerment - Roy Setiawan; Ahmad Mujaddid Fachrurreza; Maudy Noor Fadhlia; Zhillan Zhalila Fahlevi (Jurnal Ilmu Sosial Indonesia (JISI), 2025)
Abstract. This study investigates the implications of the ASEAN Free Trade Area (AFTA) on gender equality and women's empowerment in Southeast Asia, focusing on the effects of economic liberalization on women's access to economic opportunities and the persistence of structural inequalities. Utilizing a qualitative approach grounded in feminist economics and intersectionality, the research reveals that while AFTA has facilitated regional economic growth, it has not equitably benefited women, who continue to face systemic barriers in employment, wage equity, and access to resources. Women are often confined to precarious jobs in labor-intensive sectors, and their contributions, particularly in unpaid care work, remain undervalued. The findings highlight the intersectionality of gender with other social identities, complicating women's experiences under economic liberalization. The study underscores the need for gender-responsive policies that address the unique challenges faced by women in the labor market, emphasizing that integrating gender considerations into economic frameworks is essential for achieving equitable economic outcomes.  Keywords: AFTA, Gender Equality, Women's Empowerment, Economic Liberalization, Feminist Economics, Intersectionality.  Abstrak. Penelitian ini menyelidiki implikasi dari Kawasan Perdagangan Bebas ASEAN (AFTA) terhadap kesetaraan gender dan pemberdayaan perempuan di Asia Tenggara, dengan fokus pada dampak liberalisasi ekonomi terhadap akses perempuan pada peluang ekonomi dan ketimpangan struktural yang terus berlanjut. Menggunakan pendekatan kualitatif yang berlandaskan ekonomi feminis dan interseksionalitas, penelitian ini mengungkapkan bahwa meskipun AFTA telah memfasilitasi pertumbuhan ekonomi regional, hal ini belum memberikan manfaat yang setara bagi perempuan, yang terus menghadapi hambatan sistemik dalam pekerjaan, kesetaraan upah, dan akses terhadap sumber daya. Perempuan sering terjebak dalam pekerjaan yang tidak stabil di sektor-sektor yang padat karya, dan kontribusi mereka, terutama dalam pekerjaan perawatan yang tidak dibayar, tetap tidak dihargai dengan semestinya. Temuan-temuan ini menyoroti interseksionalitas gender dengan identitas sosial lainnya, yang memperumit pengalaman perempuan di bawah liberalisasi ekonomi. Penelitian ini menekankan pentingnya kebijakan yang responsif terhadap gender yang dapat mengatasi tantangan unik yang dihadapi perempuan di pasar tenaga kerja, dengan menegaskan bahwa mengintegrasikan pertimbangan gender ke dalam kerangka ekonomi sangat penting untuk mencapai hasil ekonomi yang adil.  Kata Kunci: AFTA, Kesetaraan Gender, Pemberdayaan Perempuan, Liberalisasi Ekonomi, Ekonomi Feminis, Interseksualitas.